Development and validation of the Chinese‐language version of the eating pathology symptoms inventory. Issue 7 (14th July 2015) - Tang, Xiaoqi; Forbush, Kelsie T.; Lui, P. Priscilla
ABSTRACT Objective Eating disorders are becoming increasingly prevalent among individuals from non‐Western countries, yet few non‐English‐language measures of eating pathology exist. The current study sought to develop and validate a Chinese version of the Eating Pathology Symptoms Inventory1 with cross‐cultural equivalence. Method The Chinese version of the Eating Pathology Symptoms Inventory (CEPSI) was translated and back‐translated by native Chinese speakers, and administered to a pilot sample of native Chinese speaking students (N = 45) from a Midwestern university in the United States. The measure was revised based on participant's feedback, and administrated to a large sample of native Chinese speakers recruited from a Midwestern community (N = 195; 49.2% women) to test the factor structure and convergent and discriminant validity of the measure. Results As hypothesized, the CEPSI had a robust eight‐factor structure, and demonstrated evidence for acceptable internal consistency (median coefficient alphas were 0.80 for men and 0.79 for women, and alpha values ranged from 0.36 to 0.85 in men and 0.70 to 0.89 in women), and good convergent validity (correlations with relevant translated scales from the Eating Disorder Examination‐Questionnaire and the Eating Attitudes Test‐26 ranged from 0.22 to 0.58) and discriminate validity (correlations with a translated version of the Center for Epidemiological Studies – Depression Scale ranged from .12 to .30). Discussion Results indicate that the CEPSI has high potential value as a new self‐report measure of eating pathology that can be used in future research and clinical settings to assess eating disorder‐related psychopathology among Chinese speaking individuals. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:1016–1023).